2017
DOI: 10.3390/su9091647
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue: “Maintaining Ecosystem Services to Support Urban Needs”

Abstract: Cities are growing worldwide, in their geographical extent with respect to their general and current macro-economic significance, as well as regarding their total populations. Thereby, land and resource utilization are increasing in and around agglomeration centers, as are the requirements for a good quality of life and health. Current projections of rapid expansion of urban areas present fundamental challenges but also opportunities to design more livable, healthy, and resilient cities [1,2].Often, the city h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 27 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…Today, urban areas represent a fundamental tool to support and promote sustainable development within urban contexts [69]. As highlighted by the systematic review, the scientific literature has shown a growing interest in urban green areas from 2006 to 2020 (Figure 2a).…”
Section: Discussionmentioning
confidence: 99%
“…Today, urban areas represent a fundamental tool to support and promote sustainable development within urban contexts [69]. As highlighted by the systematic review, the scientific literature has shown a growing interest in urban green areas from 2006 to 2020 (Figure 2a).…”
Section: Discussionmentioning
confidence: 99%
“…Urbanization, another example of extrinsic factors, alters soils in various ways (e.g., erosion and pollution) and creates ES/ED specific to urban soil diversity (urban pedodiversity), which requires adjustment of valuations to urban environments [56,57]. Urbanization alters the stocks and flows of ES/ED provided by soils in urban and non-urban environments since urban environments are not self-supporting, which creates a significant demand for ES from urban fringes and beyond [58].…”
Section: Extrinsic Factors: Examples Of Monetary Valuations Based On Interaction Of Soil Diversity (Pedodiversity) and The Earth's Spherementioning
confidence: 99%
“…Furthermore, ecological environmental protection, that is, creating environmental value, must also be considered. Therefore, the relevant decision-making requires the proper management of ecological and land use through project priority setting [36]. In order to balance the aspects of economic, social, and environmental value, China's resource-based cities generally optimize the industrial value chain structure by adjusting industrial structures.…”
Section: Theoretical Modelsmentioning
confidence: 99%